Exploring the ancient wisdom and modern relevance of Chinese medicine: A comprehensive review - Kuldeep Singh; Jeetendra Kumar Gupta; Divya Jain; Shivendra Kumar; Talever Singh; Sunam Saha (Elsevier, 2024)
Introduction: Chinese medicine, rooted in a rich history dating back thousands of years, offers a holistic approach to healthcare that has endured the test of time. This comprehensive review explores the ancient wisdom and modern relevance of Chinese medicine, shedding light on its principles, practices, and adaptability in contemporary healthcare. Methods: This review employs a multidisciplinary approach, drawing upon ancient texts, modern scientific research, and clinical studies to elucidate the core tenets of Chinese medicine. A comprehensive literature search was conducted in various databases, including PubMed, Web of Science, and traditional Chinese medical databases, to identify relevant articles, books, and historical documents. Results: The review synthesizes the fundamental concepts of Chinese medicine, such as Qi, Yin-Yang, the five elements, and meridian system, while examining their physiological and clinical significance in the context of modern medicine. It also delves into the integration of Chinese Medicine into mainstream healthcare systems worldwide, highlighting its growing acceptance and utilization in the treatment of various conditions, including chronic pain, mental health disorders, and complementary cancer care. Discussion: The discussion section explores the synergy between traditional Chinese medicine and contemporary medical practices, emphasizing the potential for a complementary approach that bridges the gap between Eastern and Western healthcare. It addresses the challenges and opportunities in integrating Chinese medicine into evidence-based medicine, emphasizing the importance of rigorous research and standardization. Conclusion: In conclusion, this review underscores the enduring wisdom of Chinese medicine, showcasing its adaptability and relevance in the modern healthcare landscape. It advocates for continued collaboration between traditional Chinese medicine and conventional medical systems, fostering a more holistic and patient-centered approach to healthcare. By embracing the ancient wisdom of Chinese medicine alongside modern medical advancements, we can pave the way for a healthier and more balanced future.